The Film of Chitosan-ZnO Nanoparticles-CTAB : Synthesis, Characterization and In Vitro Study - Ahmad Fatoni; Herlina Silvia Yessica; Aldilah; Mia Almi; Agnes Rendowaty; Romsiah; Lasmaryna Sirumapea; Nurlisa Hidayati (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2022)
The synthesis of film chitosan- ZnO nanoparticles-CTAB were studied. The aims of this research were synthesis of the film chitosan-ZnO nanoparticles-CTAB, its characterization and, application of the film chitosan-ZnO nanoparticles-CTAB as an antibacterial of Staphylococcus aureus. The film of chitosan-ZnO nanoparticles-CTAB was synthesized by the casting method and characterized by FTIR spectroscopy and X-ray diffraction, respectively. The film of chitosan-ZnO nanoparticles-CTAB was used as an antibacterial agent with the agar disk diffusion method. The result showed that the Zn-O group at the film of chitosan-ZnO nanoparticles-CTAB was detected at a wavenumber between 578-619 cm-1. The band at 2852.72-2854.65 cm-1 is the band of C-H groups in the film of chitosan-ZnO nanoparticles-CTAB. The effect of ZnO nanoparticles-CTAB changed of the physical structure of chitosan. The average of the inhibition zone in the film of chitosan-ZnO nanoparticles-CTAB I, II and III was 10.37 ± 0.55, 11.31± 1.27 and 10.38 ± 0.24 mm respectively.